The normal evolution of the cranium in three dimensions. Issue 6 (June 2020) - Meulstee, J.W.; de Jong, G.A.; Borstlap, W.A.; Koerts, G.; Maal, T.J.J.; Delye, H.
Abstract: Insight into the growth and development of the normal newborn cranial shape is essential to monitor cranial development, to detect and diagnose abnormal skull shapes, and for the long-term follow-up of craniosynostosis surgery. The aim of this study was to analyse the growth pattern of the cranial shape of infants during the first years of life using 3D stereophotogrammetry and 3D computed tomography (CT) with advanced 3D evaluation techniques. A large set of 3D photographs ( n  = 199) and CT scans ( n  = 183), taken between ages 0 and 54 months, was collected. Cranial shapes with artefacts and asymmetries were removed. Total volumes and intracranial volumes were obtained, as well as 3D and 2D measurements, including the cranial width, cranial length, cranial index, and suture lengths. Growth maps were created for all modalities to indicate 3D growth over time. For the final analysis, a total of 130 3D photographs, 94 hard tissue CT scans, and 76 soft tissue CT scans were used. 3D and 2D measures, volumes, growth maps, and growth animations were obtained. A non-uniform growth was revealed by the 3D growth maps. This study addresses the need for normative cranial evolution data to monitor healthy cranial development and for detection, follow-up, and treatment planning in craniosynostosis.